Construction aerodynamics of cable-stayed bridges for record spans: Stonecutters Bridge. (November 2016) - Sham, S.H. Robin; Wyatt, Tom A.
Abstract: This paper presents the extensive aerodynamic investigations conducted for the construction of the 1018 m-main span Stonecutters Bridge. The emphasis is on the behaviour of the bridge structure during the erection stages, notably its response to vortex shedding, buffeting and divergent amplitude effects. A description is given of the principal aspects of the wind tunnel testing carried out, including section model testing, aeroelastic freestanding tower model testing on different erection heights, and aeroelastic bridge model testing to investigate the bridge erection stages. The engineering implications of the results are discussed. Wind tunnel testing on stay cables has also been carried out, with special reference to determining cable drag and the susceptibility to rain-wind induced oscillations. These investigations advanced general understanding of the behaviour of cable-stayed bridges during construction, and contributed significantly to the development of the erection method and sequence for the Stonecutters Bridge leading to the expeditious completion of this work.